Misguided investments in meeting Millennium Development Goals: a reconsideration using ends-based - James, Jeffrey (2006)
This paper contends that some of the Millennium Development Goals do not distinguish between potential and actual achievements. In the case of education for insurance, the completion of primary education by all students is not an end in itself, but rather an intermediary phase in the process of learning to read and wriyte, and so on. Thus, meeting the stated Millennium Development Goal may in fact do little or nothing to enhance these more ultimate achievements. Using other, similar examples, we suggest that governments need to consider moving from means-to ends-based proxies, and in so doing, to reconsider whether the way that resources are allocated in any given sector is in fact the optimal one. - Reproduced.
Keywords: Millennium Development Goals